PENGARUH KUALITAS LAYANAN DAN PENANGANAN KOMPLAIN TERHADAP LOYALITAS NASABAH KREDIT DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI PADA PD. BKK CABANG DEMPET KOTA KABUPATEN DEMAK (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the influence of the quality of service and handling of complaints against credit customer loyalty and satisfaction as mediating variables in PD. BKK City Branch Dempet Demak. The research sample of 100 respondents, the sampling technique used purposive sampling method of sampling with a predetermined set of criteria, The results show that (1) there is a positive and significant effect of service quality on satisfaction, (2) there is a positive and significant effect of handling complaints against complacency, (3) there is a positive and significant effect of service quality on customer loyalty, (4) there is a positive and significant influence between the handling of complaints on customer loyalty, (5) there is a positive and significant effect of satisfaction on customer loyalty, (6) The findings of the first mediation effect of satisfaction in mediating the effect of Quality of Service on Customer Loyalty obtained that satisfaction does not mediate the effect of Service Quality on Customer Loyalty, (7) The results of the mediation effect shows that satisfaction does not mediate the effect Handling of Complaints against the Customer Loyalty. Keywords : quality of service, handling complaints, satisfaction and customer loyalty